2010
DOI: 10.1097/mjt.0b013e3181d69072
|View full text |Cite
|
Sign up to set email alerts
|

A Phase IIIb, Randomized, Double-blind, Placebo-controlled, Multicenter Study Evaluating the Safety and Efficacy of Dexmedetomidine for Sedation During Awake Fiberoptic Intubation

Abstract: GABA-mediated sedatives have respiratory depressant properties that may be detrimental in patients with difficult airways. In this randomized, double-blind, multicenter, Phase IIIb Food and Drug Administration study, safety and efficacy of dexmedetomidine compared with placebo were evaluated as the primary sedative for awake fiberoptic intubation (AFOI). Patients were randomized to receive dexmedetomidine or saline. Patients were sedated with dexmedetomidine or rescue midazolam to achieve targeted sedation (Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 23 publications
0
40
0
1
Order By: Relevance
“…As a more highly selective α 2 -adrenoreceptor agonist than clonidine, dexmedetomidine has been shown to blunt haemodynamic responses during intubation and extubation whilst the patient is conscious. 27,28 In the present study, patients sedated with dexmedetomidine displayed fewer sympathetic responses to bronchoscopy compared with those sedated with midazolam. Fox et al 29 concluded that adequate midazolam-alfentanil sedation could blunt the sympathetic response to bronchoscopy, and that prophylactic labetalol had no additional advantageous effects on haemodynamic stability.…”
Section: Dexmedetomidine Versus Midazolam Sedation In Bronchoscopymentioning
confidence: 71%
“…As a more highly selective α 2 -adrenoreceptor agonist than clonidine, dexmedetomidine has been shown to blunt haemodynamic responses during intubation and extubation whilst the patient is conscious. 27,28 In the present study, patients sedated with dexmedetomidine displayed fewer sympathetic responses to bronchoscopy compared with those sedated with midazolam. Fox et al 29 concluded that adequate midazolam-alfentanil sedation could blunt the sympathetic response to bronchoscopy, and that prophylactic labetalol had no additional advantageous effects on haemodynamic stability.…”
Section: Dexmedetomidine Versus Midazolam Sedation In Bronchoscopymentioning
confidence: 71%
“…It has the advantage of only causing mild respiratory depression at higher doses but does have sympathomimetic and vagolytic actions that may lead to bradycardia and hypotension [83]. These features are useful to attenuate the sympathetic response to intubation which it has been shown to do safely and effectively in flexible bronchoscopy for awake intubation [84] and in upper and lower gastrointestinal endoscopy [85][86][87], but it does require continuous cardiovascular monitoring to avoid unwanted complications. For upper gastrointestinal endoscopy dexmedetomidine resulted in a shorter recovery time and increased patient satisfaction when compared to midazolam [86].…”
Section: Dexmedetomidinementioning
confidence: 99%
“…Many agents have been reported to provide sedation for intubation including fentanyl, ketamine, midazolam, remifentanil, propofol, and dexmedetomidine. [1][2][3][4][5] Dexmedetomidine, an α2-adrenoceptor agonist, may be a wondrous drug for use during fiberoptic intubation as it produces sedation and analgesia without concomitant depressing respiratory function. 6,7 Thus, dexmedetomidine possess numerous properties that make it a convenient drug for use in managing patients with difficult airways.…”
Section: Introductionmentioning
confidence: 99%